Pronouns Are as Sensitive to Structural Constraints as Reflexives in Early Processing: Evidence From Visual World Paradigm Eye-Tracking - Han, Chung-hye (Front Psychol, 2021)
A number of studies in the extant literature report findings that suggest asymmetry in the way reflexive and pronoun anaphors are interpreted in the early stages of processing: that pronouns are less sensitive to structural constraints, as formulated by Binding Theory, than reflexives, in the initial antecedent retrieval process. However, in previous visual world paradigm eye-tracking studies, these conclusions were based on sentences that placed the critical anaphors within picture noun phrases or prepositional phrases, which have independently been shown not to neatly conform to the Binding Theory principles. We present results from a visual world paradigm eye-tracking experiment that show that when critical anaphors are placed in the indirect object position immediately following a verb as a recipient argument, pronoun and reflexive processing are equally sensitive to structural constraints.